A proposed development plan for the Church of the Risen Lord (CRL) Library at the University of the Philippines Diliman - Tayam, Tiana Rose Norfi N. (School of Library and Information Studies, University of the Philippines Diliman, 2018)
With the aim of contributing to the existing research literature of church libraries, this study examined the Church of the Risen Lord (CRL), an interdenominational Christian community located inside the University of the Philippines Diliman, and proposed a development plan for the church’s library.